Kajian Profil Ekonomi Desa Wisata Ngerangan Sebagai Upaya Pengentasan Kemiskinan - Nophia Gaby Damayanti; Landung Esariti; Maya Damayanti; Hadi Wahyono (REKA RUANG, 2021)
The potential of the tourism industry is an option for poverty alleviation efforts by opening up jobs and increasing income. Ngerangan Tourism Village is one of the poorest areas in Klaten Regency which has developed a tourism business since 2019 through empowerment of tourism actors. This article aims to examine the economic profile of the Ngerangan Tourism Village in the implementation of the tourism village program as an effort to alleviate poverty, by looking at 2 indicators, namely community empowerment activities and tourism activities. The research was conducted through a survey by distributing questionnaires to 42 samples of tourism actors using quantitative methods. Interviews were also conducted with 2 resource persons representing BUMDES and DISPARBUDPORA. The results of the study clearly show that empowerment activities are able to increase community knowledge and participation in tourism village development activities. While the analysis of tourism activities, shows an increase in PAD (Regional Income) by Rp. 5,000,000 / year from tourism contributions, the emergence of 7 thematic villages as tourism products offered, and the increase in specific types of work related to tourism services such as chefs, cashiers, homestay rentals and others.